Association Between Nurses' Workload and Compliance with Digital NEWS Documentation: A Cross-Sectional Study - Widiastuti, Linda; Atrie, Utari Yunie; Wati, Liza; Sugiharto, Firman (Journal of Applied Nursing and Health, 2026)
Background: Deterioration in a patient's clinical condition can occur suddenly during hospitalization, making early detection essential to prevent delayed interventions and reduce mortality risk. Patient deterioration requires early detection using the National Early Warning Score (NEWS). However, its implementation is often reported to be associated with nurses' high workload. Furthermore, limited evidence exists on how workload influences digital NEWS documentation, particularly in resource-constrained settings. This study aimed to determine the relationship between workload and the implementation of digital NEWS documentation. Methods: This quantitative, cross-sectional study followed the STROBE guidelines and involved 72 nurses selected via convenience sampling at a Type A private hospital in Indonesia. The independent variable was workload, and the dependent variable was digital NEWS documentation. Data were collected using a validated workload questionnaire and a digital NEWS documentation checklist based on Royal College of Physicians (2017) standards, and analyzed using Jamovi software via Chi-square tests. Results: 76.4% of respondents experienced a non-heavy workload, and 65.3% implemented digital NEWS documentation. The analysis revealed a significant relationship between workload and the implementation of digital NEWS documentation (p = 0.003; OR = 0.186; CI95% = 0,058-0,597), indicating that a heavier workload was associated with a lower likelihood of completing NEWS documentation. Conclusion: These findings highlight that workload is significantly associated with clinical documentation compliance. To enhance patient safety, hospital administrators must move beyond general evaluations and implement targeted interventions, including staffing adjustments to balance nurse-to-patient ratios, workflow redesign to minimize administrative burden, and digital optimization of the digital NEWS system to streamline data entry.